ETOS KERJA PEKERJA HARIAN LEPAS (STUDI KASUS BURUH PANEN PADA PERKEBUNAN KELAPA SAWIT PT. WANASARI NUSANTARA DI KABUPATEN KUANTAN SINGINGI) - Sri Mulliyani; Indrawati " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Industry made a lot ofchanges to the society living sectors, where was the presence ofindustry many job vacancy created. The company provided jobs based on the expertise each person. Majority of society around the company had skill in hervesting and cause them chose to become harvest laborers. Weber’s work about The Protestan Ethnic and Spirit Capitalism showed well relationship between religion doctrin with spirit capitalism. Then Protestan doctrine uttered this Weber’s work has carried the implication for growing a new ethos in Protestan community. The ethos was directly related with the spirit of hard work for arrogated the world successfully. The framework of this research was company provided job vacancy. If the laborers workeveryday, so they would got full salary. The work ethos was consisted of laborer’ time discipline and hard work. The research took place PT. Wanasari Nusantara with the reason that many free daily workers especially harvest laborer who had tenacity in hight sufficient. The total of whole harvest laborers was 27 people. The techniquesof collecting data was observation. Questionnaite and taking picture for suported the result of research. Afterwards, the data served in the form of table and processed in quantitative-descriptive meant in the form of table then explained clearly. After analyzed, apparently the work ethos of harvest laborers in the company was very high. They work everyday for getting full salary and able to fulfilled the living needs, and they also enjoyed their jobs this time as harvest laborersKeywords: Industry,Work Ethics, Laborers